The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1302/2058-5241.2.170007
|View full text |Cite
|
Sign up to set email alerts
|

‘On-track’ and ‘off-track’ shoulder lesions

Abstract: Shoulder stability depends on the position of the arm as well as activities of the muscles around the shoulder. The capsulo-ligamentous structures are the main stabilisers with the arm at the end-range of movement, whereas negative intra-articular pressure and concavity-compression effect are the main stabilisers with the arm in the mid-range of movement.There are two types of glenoid bone loss: fragment type and erosion type. A bone loss of the humeral head, known as a Hill-Sachs lesion (HSL), is a compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 40 publications
1
72
0
4
Order By: Relevance
“…T he current prognostic study retrospectively evaluating the effectiveness of the Glenoid Track Instability Management Score (GTIMS) concludes that the GTIMS is a more refined prognosticator of which shoulder instability patients require the Latarjet procedure than the Instability Severity Index Score (ISIS) published in 2007. 1 The GTIMS incorporates the "ontrack" and "off-track" concept 2,3 with the same "nonbone loss" clinical risk factors in the ISIS scoring system (aged < 20 years, 2 points; competitive sports participation, 2 points; overhead or contact sports participation, 1 point; and shoulder hyperlaxity, 1 point). In the GTIMS, on-track lesions receive 0 points whereas offtrack lesions receive 4 points.…”
Section: See Related Article On Page 56mentioning
confidence: 99%
See 1 more Smart Citation
“…T he current prognostic study retrospectively evaluating the effectiveness of the Glenoid Track Instability Management Score (GTIMS) concludes that the GTIMS is a more refined prognosticator of which shoulder instability patients require the Latarjet procedure than the Instability Severity Index Score (ISIS) published in 2007. 1 The GTIMS incorporates the "ontrack" and "off-track" concept 2,3 with the same "nonbone loss" clinical risk factors in the ISIS scoring system (aged < 20 years, 2 points; competitive sports participation, 2 points; overhead or contact sports participation, 1 point; and shoulder hyperlaxity, 1 point). In the GTIMS, on-track lesions receive 0 points whereas offtrack lesions receive 4 points.…”
Section: See Related Article On Page 56mentioning
confidence: 99%
“…Similarly, Yang et al 9 reported that in 189 patients with recurrent anterior shoulder instability with off-track Hill-Sachs lesions and less than 25% glenoid bone loss, an arthroscopic Bankart procedure with remplissage achieved equivalent subjective results and revision rates to the Latarjet procedure. Finally, it is interesting that Itoi 3 opined that an arthroscopic Bankart procedure with remplissage may be a good procedure for off-track Hill-Sachs lesions with glenoid bone loss of less than 25%. His exceptions to this are overhead throwing athletes and contact or collision athletes.…”
Section: See Related Article On Page 56mentioning
confidence: 99%
“…Many factors impact the incidence of recurrent instability 7 ; they include symptom duration, number of dislocations (especially 5 or more), revision cases, Hill-Sachs lesion sizes, glenoid bone loss, and "on-track" or "off-track" lesions. [7][8][9] The instability severity index score 10,11 and glenoid track instability management score 12 scoring systems include meaningful prognostic factors impacting surgical outcomes that were not appreciated in earlier case series: younger than 20 years of age, competitive sports participation, overhead or contact sports, and shoulder hyperlaxity. Significant glenoid bone loss is perhaps the most widely appreciated variable.…”
Section: See Related Article On Page 862mentioning
confidence: 99%
“…An on-track/ off-track determination was made using standard and prior well-referenced techniques. [7][8][9][10] Overall, the authors are to be congratulated for using multiple observers for the determination of these measurements. The average surface area from the circle method on CT scan was 18.4% and on MRI was 16.8%.…”
Section: See Related Article On Page 12mentioning
confidence: 99%